Pancreatectomy for Intraductal Papillary Mucinous Neoplasm of the Pancreas: Could Pancreaticogastrostomy Be the Anastomosis of Choice? - Gourgiotis, Stavros; Salemis, Nikolaos S; Kanakopoulos, Dimitrios; Germanos, Stylianos (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: 401 General Army Hospital of Athens. Athens, Greece.